Transcriptional regulatory factor AHA_4052 regulates aminoglycoside resistance in Aeromonas hydrophila - Li, Wanxin; Tu, ZhiWei; Zhang, Huaiyao; Lu, Binrong; Liu, Fang; Lin, Xiangmin; Wang, Guibin (Frontiers in Microbiology, 2025)
IntroductionWith the increasing identification of multidrug resistance in Aeromonas hydrophila isolated from diverse food sources, there is an urgent need to investigate its resistance mechanism. Previous studies have demonstrated that OmpR/PhoB-type response regulators (RRs) play critical roles in mediating bacterial tolerance to various environmental stresses.Methods and resultsIn this study, we constructed an AHA_4052 gene knockout strain, a member of the OmpR/PhoB family of DNA-binding response regulators, and studied its phenotypic characteristics. Deletion of the AHA_4052 gene rendered the bacteria significantly more sensitive to high temperature, osmotic stress, and aminoglycoside antibiotics compared to the wild-type A. hydrophila. Label-free quantitative proteomic analysis revealed 131 differentially expressed proteins in the ΔAHA_4052 mutant strain. These proteins were predominantly associated with ribosome, butanoate metabolism, and glycerophospholipid metabolism pathways, with ribosome-related proteins accounting for 17.56% of the total. Additionally, seven antibiotic resistance-related proteins exhibited significant expression changes in the mutant strain. Chromatin immunoprecipitation assay–polymerase chain reaction (ChIP-PCR) validation further demonstrated that the transcriptional regulator AHA_4052 directly binds to the promoters of two resistance genes, AHA_2114 and AHA_3488.DiscussionCollectively, these findings indicate that the transcriptional regulatory factor AHA_4052 plays a critical role in stress tolerance, particularly against aminoglycosides, providing insights into the resistance mechanisms of A. hydrophila and potentially informing the development of new therapeutic strategies.